"The Weight on Our Shoulders Is Too Much, and We Are Falling". (14th May 2013) - Kral, Michael J.
<x xml:space="preserve">Abstract</x> Inuit youth suicide is at an epidemic level in the circumpolar north. Rapid culture change has left Inuit in a state of coloniality that destabilized their kin‐based social organization, and in spite of advances in self‐governance social problems such as suicide continue. Drawing on ethnographic fieldwork I carried out in Nunavut, Canada (2004–2005), including 27 interviews with Inuit between the ages of 17 and 61, I examine male youth in particular in the context of recent colonial change, gender ideologies and behavior, youth autonomy, and the family. Anger is common among Inuit male youth, often directed toward girlfriends and parents, and suicide is embedded in some of these relationships. Many Inuit male youth are struggling with a new cultural model of love and sexuality. Inuit speak about a need for more responsible parenting. Evidence is beginning to show, however, that local, community‐based suicide prevention may be working.